A Grounded theory study of the intention of nurses to leave the profession - Leyla Alilu; Vahid Zamanzadeh; Leila Valizadeh; Hosein Habibzadeh; Mark Gillespie
ABSTRACT Objective: this study explores the process of the development of an intention to leave bedside nursing. Method: the process was studied from the perspective of 21 nurses using the grounded theory method. Data were collected using semi-structured interviews and the constant comparative method of Corbin and Strauss was used for data analysis. Results: according to the participants, the two main categories, "social image of nursing", and "culture and structure of the bedside", were the contextual factors that influence why nurses are leaving bedside care provision. Disappointment with a perceived lack of progress or improvement in the clinical experience formed primary psychosocial concerns for the participants. Competence and a process of self-control were steps taken by the participants. These, associated with interventional conditions produced the outcomes of the loss of professional commitment and desire to leave bedside nursing. "Failure to integrate personal expectations with organizational expectations: in search of escape" was the central category of the study that linked the categories together. Conclusion: the findings of this study provide useful information about the needs of nurses for overcoming the intention to leave bedside care. The identification of this process can help in recognizing emerging problems and providing solutions for them.